Acute Antibody-Mediated Rejection and its Treatment in Kidney Transplantation: Report from a National Cohort Study. (July 2018) - Perrottet, Nancy; Golshayan, Dela; Rotman, Samuel; Moll, Solange; Hopfer, Helmut; Catana, Emmanuelle; Koller, Michael; Venetz, Jean-Pierre; Aubert, Vincent; Vionnet, Julien; Manuel, Oriol; Bühler, Léo; et al.
Abstract : Swiss Transplant Cohort Study (STCS). Background: The management of antibody mediated rejection (AMR) remains nowadays a major challenge in kidney transplantation. Different therapeutic strategies are used but more data are needed to define the optimal treatment. This is the first report of the treatment of acute AMR in kidney transplant recipients in a real-life multicenter cohort study setting. Methods: Kidney transplant recipients (May 2008 – 2014) who received a treatment for an acute AMR episode occurring in the first year posttransplantation (post-Tx) were included from the Swiss Transplant Cohort (STCS). The main objectives were to describe the treatment used and to analyze the outcomes in term of efficacy (serum creatinine at 3 months post-acute AMR) and safety (incidence of infectious complications within 6 months post-acute AMR). Results: Overall, 64/1669 (3.8%) patients were treated for an acute AMR occurring in the first year post-Tx (74 episodes in total). In addition to corticosteroid boluses, the most common treatment modalities used were Plasma exchange or pheresis (55.4%) and IVIG (39.2%) followed by rituximab (25.7%) and antithymocytes globulins (23.0%), and finally eculizumab (4.1%) and bortezomid (4.1%). Most acute AMR were managed with bitherapy (43.2% of episodes), mostly corticosteroids and plasmapheresis, but as much as 5 therapies were used in combination in few patients (n=4). At 3 months post-rejection, the treatments used were overall effective with a full recovery of allograft function in 67.6% of the cases. In patients with de novo DSA (n=7), this proportion reached 85.7% compared to 56.0% in patients with preformed DSA (n=50) (not significant). The graft loss at 1-year was 9.2% (6/65), the majority related to ongoing rejection. At 12 months post-Tx, 33.3% of the patients cleared all DSA (11/33). In patients with de novo DSA (n=7), the clearance reached 71.4%, compared to 23.8% in patients with preformed DSA (n=21) (p=0.02). The treatments of acute AMR were followed by at least one infectious complication in the following 6 months in 63.6% of cases. The overall incidence of viral infections was 71.2% (47/66), with 13.6% of CMV diseases and 7.6% of BK viremia. The bacterial and fungal infectious complications reached 43.9% and 7.6% respectively. At 1-year, patient survival was 93.7%. Two patients died due to severe infectious complications (3.1%). Conclusions: In this multicenter national cohort study, we found a wide variety of therapeutic strategies used to treat acute AMR, supporting the need for more controlled trials in the management of acute AMR. Despite this heterogeneity in the treatments used, the graft survival at 1-year reached 91%, with an overall good response to therapy at 3 months. However, infectious complications were common, including severe infections rarely leading to patient loss.